AHP TOPSIS METHOD FOR DECISION MAKING IN CHOOSING QUALITY SUNSCREEN PRODUCTS - Sofian, Erza; Aprilianta, Kylix Rizky (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
The number of new Sunscreen products due to the importance of using Sunscreen with high quality and affordable prices, this will certainly make it difficult for users to make the right choice, according to the criteria they want. So, this research helps users determine the best Sunscreen products. This study combines 2 (two) methods, namely, AHP and TOPSIS without any comparison in both methods. Data were collected by means of observations, interviews, and questionnaire dissemination. The number of informants in the study was 10 (ten) people as experts in the field of facial care. There were 8 (eight) informants who gave similar answers. Then fill in the pairwise comparison form to the informant. Then, Calculations with Excel, and Super Decision Software. The results showed that the one with the highest priority on the criteria factor with AHP calculation was White Cast with a weight of 0.34. While the first alternative ranking with the calculation of the TOPSIS method is something with a value of 0.59, Madame Gie with a value of 0.52, Emina with a value of 0.36, and Wardah with a value of 0.07. For that something products can be recommended as quality Sunscreen. Keywords : Decision Support System, Sunscreen Selection, AHP, TOPSIS